The Lectin-Like Oxidized Low-Density Lipoprotein Receptor-1 and Cardiovascular Disease - Sheikh, MSA; Yang, T; Salma, U; Ali, M (Cardiovascular Journal, 2011)
Lectin-like oxidized LDL receptor-1 (LOX-1), a lectin-like 50-kD receptor for oxidized low-density lipoproteins (ox-LDL), is present primarily on endothelial cells. Oxidatively modified low-density lipoprotein (oxLDL) is implicated in the pathogenesis of atherosclerosis. Endothelial dysfunction is the initial change in the vascular wall that induces morphological changes for atheroma-formation. LOX-1 was identified as the receptor for oxLDL that was thought to be a major cause of endothelial dysfunction. LOX-1 has been demonstrated to contribute not only to endothelial dysfunction, but also to atherosclerotic-plaque formation, hypertension, myocardial infarction and intimal thickening after balloon injury. Studies with transgenic and knockout mouse models have elucidated in part the role of LOX-1 in the pathogenesis of atherosclerosis and cardiac remodeling. Recently, a circulating soluble form of LOX-1(sLOx-1), corresponding solely to its extracellular domain, has been identified in human serum. Circulating levels of sLOX-1 are increased in inflammatory and atherosclerotic conditions and are associated with acute coronary syndrome, with the severity of coronary artery disease, and with serum biomarkers for oxidative stress and inflammation, suggesting that they could be useful marker for vascular injury. Identification and regulation of this receptor and understanding of signal transduction pathways might open new gateways from diagnosis to therapeutics for cardiovascular diseases. Keywords: Atherosclerosis; Endothelial dysfunction; LOX-1; ox-LDL; Signal transduction. DOI: http://dx.doi.org/10.3329/cardio.v3i2.9187 Cardiovasc. J. 2011; 3(2): 169-177